THE EFFECT OF SOMATIC, AUDITORY, VISUAL AND INTELLECTUAL MODELS (SAVI) TOWARD CRITICAL THINKING ABILITY - Lailiyah, Alina Nur; Simbolon, Marlina Eliyanti; Hermawati, Eli (The University of Kuningan, 2023)
ABSTRACTThe problem in this research is motivated by students' low critical thinking skills due to different learning styles, passive and not conducive. The purpose of this study was to describe the differences in students' critical thinking skills and the differences in the improvement of students' critical thinking skills in social studies content using somatic, auditory, visual and intellectual (SAVI) models. The research approach used in this study is a quantitative approach using the experimental method, namely quasi-experimental with the research design, namely nonequivalent control group design with a pretest before treatment and posttest after treatment. It consists of two important variables, namely the dependent variable (Y) critical thinking skills and the independent variable (X) somatic, auditory, visual and intellectual models (SAVI). This research was conducted in class V in the even semester of SD Negeri 4 Kuningan for the 2022/2023 academic year, with 40 students as research subjects. Data collection techniques in this study used tests, namely descriptions based on indicators of critical thinking skills. As for the data analysis technique used in this study, namely the normality test, homogeneity test, N-gain test, t test or difference test between the critical thinking abilities of control and experimental class students as well as different tests increasing students' critical thinking skills in the control and experimental classes . The results showed that there were differences in ability and differences in the improvement of students' critical thinking skills between the experimental class which was given the somatic, auditory, visual and intellectual (SAVI) treatment model and the control class which used the discovery learning model.Keywords: SAVI learning model; critical thinking; social sciences.